The Effect of Affective Commitment to Teacher Performance Moderated by Certification Allowance - Imam Heryanto (Kontigensi : Jurnal Ilmiah Manajemen, 2019)
The background of this research comes from the phenomenon of demanding age that requires the education sector produces superior and competitive human resources to face industrial revolution 4.0. One of an effort to be taken is through vocational formal education. The purpose of this study is to determine the effect of affective commitment to vocational permanent teacher performance of government school technology and engineering in Bandung Metropolitan moderated by certification allowance. The population in this study were all permanent teachers of government vocational school in Bandung Metropolitan who already had professional teacher certification. The sampling technique used is ‘cluster proportional random sampling’ based on the cluster region, using statistical testing methods. The research method uses descriptive survey and explanatory survey, using descriptive and verification analysis. The samples were 185 of 342 respondents / certified teacher. The results of the study show there is effect of affective commitment on teacher performance was 63.8%. Furthermore, the effect of affective commitment on teacher performance moderated by certification allowance was 68.8%.